Nursing students’ knowledge on the management of peripheral venous catheters at Wollega University - Werku Etafa (PLoS ONE, 2020)
Background Adherence to the best standards of nursing practice is the fundamental principle to improve patient outcome and prevent nursing procedure related-infections. A peripheral venous catheter (PVC) is the most common invasive procedure performed in nursing care. Its poor performance could expose patients to bloodstream-related infections. The present study aimed to assess post-basic nursing students’ knowledge of evidence-based guidelines on the management of peripheral venous catheters. Methods A cross-sectional study design was conducted on May 01–03, 2019, using a convenient sample 239 among post-basic nursing students in Wollega University. Results The study result showed that nursing students’ had a low mean (4.1±1.52) of knowledge about PVC procedure management. Only 41% of the respondents have adhered to recommendations of CDC guidelines. Among the provided options of the items, none achieved 100% correct answers. The majority of nursing students (77%) responded that antiseptic handwashing is always performed before insertion of PVCs. Meanwhile, few students (5%) correctly answered that the infusion set is recommended to be removed after 96 hours when neither lipids nor blood products are administered. In multivariable regression analysis, nursing students who had received training (AOR = 2.9, 95% CI (1.6, 5.1)) and who were younger (AOR = 2.4, 95% CI (1.3, 4.3)) significantly associated with a higher score of knowledge. Conclusions This study finding shows that an overall level of knowledge of post-basic nursing students is inadequate. Measurements such as an increase in the provision of adequate training by nurses educators based on evidence-based guidelines could improve the post-basic nursing students’ knowledge.